Human Interferon Alpha2a as Anti Hepatitis B and C - Ratih A. Ningrum (Indonesian Journal of Clinical Pharmacy, 2017)
Hepatitis is an inflammation of the liver mainly caused by hepatitis viruses. There are 5 different types of hepatitis based on the infecting virus; A, B, C, D and E. Hepatitis B and C are chronic diseases that potentially develop into hepatocarcinoma and cirrhosis on unappropriate treatments. World Health Organization (WHO) stated that currently 350 million people worldwide are living with chronic hepatitis B and 150 million people are living with Hepatitis C. The mortality rate in the world due to hepatitis is about 1.5 million people per year. The human interferon alpha2a (hIFNα2a) is a therapeutic protein used as therapeutic protein for hepatitis B and C. This review discusses the hepatitis B (HBV) and C (HCV) viruses, mechanisms of hIFNα2a as antivirus through signal transduction pathway and improvement of hIFNα2a properties by protein modification. The application of recombinant hIFNα2a (rhIFNα2a) in the treatment of hepatitis B and C that recommended by European Association for The Study of Liver (EASL) and the viral resistance mechanism are also included. The status of hepatitis B and C and the development of rhIFNα2a is also described as well.Keywords: Antiviral, hepatitis, human interferon alpha2a, protein modification, viral resistance Protein Interferon Alfa-2a Manusia sebagai Anti Hepatitis B dan CHepatitis merupakan kondisi inflamasi pada hati yang terutama disebabkan oleh virus hepatitis. Berdasarkan tipe virus yang menginfeksi, terdapat lima jenis penyakit hepatitis yaitu A, B, C, D dan E. Hepatitis B dan C merupakan penyakit kronis yang berpotensi menjadi kanker hati dan sirosis jika tidak ditangani dengan baik. World Health Organization (WHO) menyatakan bahwa saat ini terdapat 350 juta orang yang terinfeksi hepatitis B dan 150 juta orang terinfeksi hepatitis C di seluruh dunia. Angka kematian yang disebabkan hepatitis mencapai 1,5 juta orang per tahun. Protein interferon alfa-2a manusia (hIFNα2a) adalah protein terapeutik yang digunakan sebagai obat hepatitis B dan C. Review ini mendiskusikan mengenai virus hepatitis B (HBV) dan C (HCV), mekanisme hIFNα2a sebagai antivirus melalui sistem transduksi sinyal dan peningkatan sifat hIFNα2a melalui modifikasi protein. Review ini juga membahas aplikasi bentuk rekombinan hIFNα2a (rhIFNα2a) dalam penanganan hepatitis B dan C yang direkomendasikan oleh European Association for The Study of Liver (EASL) dan mekanisme resistensi virus. Status hepatitis B dan C serta perkembangan rhIFNα2a juga didiskusikan lebih lanjut.Kata kunci: Antivirus, hepatitis, interferon alfa-2a manusia, modifikasi protein, resistensi virus